Detekce QRS založená na vlnkové transformaci - Zedníček, Vlastimil (Vysoké učení technické v Brně. Fakulta elektrotechniky a komunikačních technologií, 2014)
Cílem této práce je realizace detektoru QRS s využitím vlnkové transformace. První část je zaměřena na vznik a možnosti měření srdeční aktivity. V další části práce se seznámíme s různými možnostmi detekce komplexu QRS a podrobněji se věnujeme vlnkové transformaci. Ta bude využita pro návrh detektoru QRS komplexu. Praktická část se věnuje návrhu samotného detektoru v prostředí Matlab a jeho různá nastavení. Navržený detektor je testován na databázi CSE. Dosažené výsledky navrženého detektoru jsou zhodnoceny s výsledky jiných autorů.

This thesis deals with implementation of detector QRS complex with use of wavelet transform. The first part is focused on formation and possibility to measure cardiac activity. The other part of thesis we will familiarise with the different possibilities of detection QRS complex and we intimately focus on wavelet transform that will be used for a project of detection QRS complex. The practical part of thesis focuses on the project of detector in programming language Matlab and his different setting. This projected detector has been tested with CSE database. Achieved results of projected detector are evaluated with the results of others authors.
QRS detection based on wavelet transform
Keywords: Detektor; elektrokardiogram; QRS komplex; vlnková transformace; QRS detektor; Detector; electrocardiogram; QRS complex; wavelet transform; QRS detector